PENGEMBANGAN RPS-FLIP BUILDER UNTUK MENINGKATKAN PEMAHAMAN IPA DALAM PEMBELAJARAN DI MASA COVID-19 - Yunianto, Teguh (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2021)
The research aims to describe the development of the School Development Plan (RPS-Flip builder) and to find out the validity of the RPS-Flip builder in learning natural science (IPA) during the Covid-19 period. This research method is a development research with the Borg and Gall model. Product trials are carried out on a limited scale by involving students. The results of this study describe the development of the RPS-Flip-builder including the analysis of potential problems, data collection, product design, design validation, product testing, and product revision. Furthermore, the product feasibility results show that the material expert's assessment is 83.25% with the "very valid" category, the media expert is 71.66% with the "feasible" criteria, field trials with an average value of 90% with the interpretation criteria "very high. practical". Finally, the semester learning plan (RPS) using the flip builder learning media on natural science (IPA) material is feasible and very practical to use to increase understanding.